Feeding the Pelican: Using Archival Hard Drives for Cold Storage Racks - Black, Richard; Donnelly, Austin; Harper, Dave; Ogus, Aaron; Rowstron, Ant (8th USENIX Workshop on Hot Topics in Storage and File Systems (HotStorage 16), 2016)
Microsoft’s Pelican storage rack uses a new class of hard disk drive (HDD), known by vendors as archival class HDD. These HDDs are explicitly designed to store cooler and archival data, differing from existing HDDs by trading performance for cost. Our early Pelican experiences have helped some vendors define the particular characteristics of this class of drive. During the last twelve or so months we have gained considerable data on how these drives perform in Pelicans and in this paper we present data gathered from a test and a production environment. A key design choice for Pelican was to have only a small fraction of the HDDs concurrently spun up making Pelican a harsh environment to operate a HDD. We present data showing how the drives have been used, their power profile, their AFR, and conclude by discussing some issues for the future of these archive HDDs. As flash capacities increase eventually all HDDs will be archive class, so understanding their characteristics is of wide interest.